2015
DOI: 10.1095/biolreprod.115.129783
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Accelerates the Completion of Sperm Capacitation and Activates CatSper Channel in Spermatozoa from the Rhesus Macaque1

Abstract: During transit through the female reproductive tract, mammalian spermatozoa are exposed to increasing concentrations of progesterone (P4) released by the cumulus oophorus. P4 triggers massive calcium influx into human sperm through activation of the sperm-specific calcium channel CatSper. These properties of human spermatozoa are thought to be unique since CatSper is not progesterone sensitive in rodent sperm. Here, by performing patch clamp recording from spermatozoa from rhesus macaque for the first time, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 70 publications
5
29
0
Order By: Relevance
“…Furthermore, the results of sperm motility showed that only the VCL in all parameters increased significantly after CXCL12 treatment, which was consistent with the findings in other studies that not all kinetics parameters had significant changes (Sumigama et al, 2015;Armon and Eisenbach, 2011). As an important symbol of sperm motility, VCL is also a representative of hyperactivation (Rovasio, 1998; Suarez and Dai, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the results of sperm motility showed that only the VCL in all parameters increased significantly after CXCL12 treatment, which was consistent with the findings in other studies that not all kinetics parameters had significant changes (Sumigama et al, 2015;Armon and Eisenbach, 2011). As an important symbol of sperm motility, VCL is also a representative of hyperactivation (Rovasio, 1998; Suarez and Dai, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…These measurements were able to conclusively demonstrate using solid electrophysiological tools the presence of CatSper, SLO3, and Hv1 in mammalian sperm from different species (Kirichok et al 2006;Navarro et al 2007;Strunker et al 2011;Brenker et al 2012Brenker et al , 2014Sumigama et al 2015). However, T channel currents from Cav 3.2 which are readily observed in testicular sperm cells (Arnoult et al 1996;Lievano et al 1996;Publicover and Barratt 1999;Martinez-Lopez et al 2009) cannot be detected in epididymal sperm.…”
Section: Changes In Membrane Potentialmentioning
confidence: 75%
“…The A23187‐induced AR mainly involves a chemical effect on membrane fusion and the induced Ca 2+ influx through bypasses other than Ca 2+ channels (Tateno et al, ; Yuan et al, ), whereas the physiological AR involves activation of several signal transduction pathways. Recently, the sperm‐specific CatSper channel was shown to have a major role in the mechanism of P 4 ‐induced Ca 2+ influx and the sperm AR (Strunker et al, ; Sumigama et al, ; Tamburrino et al, ).…”
Section: Discussionmentioning
confidence: 99%